Shikhara above the Garbhagriha of the Suswani Mata Temple - Temples of India Project Team (Jio Institute, 2024)
Seen here is the back, west-facing elevation of the shikara (superstructure) of the Suswani Mata Temple. The shikhara is composed of a main central band flanked by two slender bands on either side. Originally built in stone, it has been painted later.